Synthesis of The new 2-[6-Nitro-2-benzothiazolylazo]-4-Amino benzoic acid Organic Reagent for Spectrophotometric Determination of Lead (II) - Mahdi Jreo, Aqeel (Al-Qadisiyah Journal of Pure Science, 2018)
A new 2-[6-Nitro-2-benzothiazolylazo]-4-amino benzoic acid (NO2BTAAB) organic reagent was synthesized. A sensitive and selective spectrophotometric method was proposed for the rapid determination of Pb(II) using (NO2BTAAB) reagent .The reaction between Pb(II) and (NO2BTAAB) reagent is instantaneous at pH=8.0 and the absorbance remains stable for over 24 hrs. The Method allows for the determination of Pb(II) over the range (0.1-5.5) Î¼g.ml-1 ,with molar absorptivity of (2.248 x 10+4)L.mol -1.cm-1 and a detection limit of 0.012 Î¼g.ml-1.Recovery and relative error values of precision and accuracy of method were found to be R.S.D=2.6% , Re=103 % , and Erel = 3 % . The properties of complex was studied and show;(M:R) ratio was 1:2 at pH=8.0 ,and the stability constant of 1.254 x 10+10 L2.mol-2 . The interferences of ions (NH4 +,Ni2+ , CrO4 2- , Ag+ , Cu2+, Hg+2 ,WO4 - 2, Zn+2, Co2+ , Mg2+ , Cd2+, Ba2+ , Bi3+) and masking agents effect on absorbance were studied